Technology transfer to other school spaces - Ángel San Martin Alonso; José Peirats Chacón (Universidade Federal de Santa Maria, 2015)
The technology transfer model offers us a perspective to analyze how schools receive incorporate technological activities and their equipment. Particularly, we analyze the innovations generated by these processes at the organizational level of schools as recipients of technology. The analyzed data belong to an investigation which is currently being performed in 12 regions on the "School 2.0 program". At this stage we handle references of descriptive statistics and some of the interviews and classroom observations from the participating centers on the "smart school". From the first analysis, it can be said that the school system follows a pattern transfer including: high dependence on the political level, more emphasis on the instrumental equipment than on knowledge and, finally, little previous preparation of the recipient organization.